2009
DOI: 10.1158/0008-5472.can-08-4780
|View full text |Cite
|
Sign up to set email alerts
|

Association between Rectal Optical Signatures and Colonic Neoplasia: Potential Applications for Screening

Abstract: Field carcinogenesis detection represents a promising means for colorectal cancer (CRC) screening, although current techniques (e.g., flexible sigmoidoscopy) lack the requisite sensitivity. The novel optical technology low-coherence enhanced backscattering (LEBS) spectroscopy, allows identification of microscale architectural consequences of the field carcinogenesis in preclinical CRC models with unprecedented accuracy. To investigate the potential clinical translatability of this approach, we obtained biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 45 publications
(62 reference statements)
5
74
0
Order By: Relevance
“…These parameters have been found to have diagnostic value for the detection of colon, pancreatic, and skin cancer. 20,[47][48][49] In this section, we will discuss the dependence of these parameters on the optical properties l * s , g, and m. Several inverse models for the calculation of these optical properties are presented in Sec. 5.…”
Section: Dependence Of Lebs Peak Properties On the Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters have been found to have diagnostic value for the detection of colon, pancreatic, and skin cancer. 20,[47][48][49] In this section, we will discuss the dependence of these parameters on the optical properties l * s , g, and m. Several inverse models for the calculation of these optical properties are presented in Sec. 5.…”
Section: Dependence Of Lebs Peak Properties On the Optical Propertiesmentioning
confidence: 99%
“…LEBS spectroscopy has previously been shown to have promise for the detection of several types of epithelial cancers. 14,19,20 These studies have shown that LEBS parameters such as the peak width, enhancement factor, and spectral dependence have diagnostic potential for cancer detection. The aim of this work is to relate the measured LEBS parameters (width, enhancement factor, and spectral dependence) to the optical properties of the scattering media.…”
Section: Introductionmentioning
confidence: 99%
“…These strategies include light scattering spectroscopy, 4,5 angle-resolved low coherence interferometry, 6,7 Raman spectroscopy, 8,9 diffuse optical spectroscopy, 10 partial wave spectroscopic (PWS) microscopy, 11,12 low-coherence enhanced backscattering, 12,13 quantitative phase microscopy, [14][15][16] and noninterferometric quantitative phase microscopy (NIQPM). 17 Cellular level observations of cancerous cells enabled by these technologies include an increase in subcellular constituent size, 4,5,7,13,14,17,18 changes in density, 7,14,17,18 alterations of the organization of this density to a more inhomogeneous state, 12,14,18 alterations in cellular metabolism, 10 and changes in biochemical composition 8 including higher concentrations of nuclear acids. 9 To date, label-free optical studies undertaking a detailed analysis of cellular physical properties in the context of cancer have been focused on measuring single parameters to establish one-dimensional biophysical signatures of cellular and/or tissue alterations due to cancer.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Combining these sensitivities with the ability to selectively interrogate different layers of tissue through implementation of a partial spatial coherence source, CBS has become a promising technique for the characterization and detection of colorectal and pancreatic cancers. 19,20 In order to accurately characterize a tissue sample using CBS, it is necessary to understand the dependencies of the peak shape on tissue structural composition. While various analytical formalisms have been developed to describe the CBS peak shape for different sample properties, each of these calculations rely on simplifying assumptions (e.g., scalar approximation 21 or double scattering 22 ) which cannot fully describe the complex sensitivities of the CBS peak.…”
Section: Introductionmentioning
confidence: 99%